High-Speed DSP and Analog System Design - Tran, Thanh T.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
High-Speed DSP and Analog System Design is based on Dr. Thanh T. Tran$1 (Bs 25 years of experience in high-speed DSP and computer systems and courses in both digital and analog systems design at Rice University. It provides hands-on, practical advice for working engineers, including: Tips on cost-efficient design and system simulation that minimize late-stage redesign costs and product shipment delays Emphasis on good high-speed and analog design practices that minimize both component and system noise and ensure system design success Guidelines to be used throughout the design process to reduce noise and radiation and to avoid common pitfalls while improving quality and reliability Hands-on design examples focusing on audio, video, analog filters, DDR memory, and power supplies The inclusion of analog systems and related issues cannot be found in other high-speed design books (3z(BThis book is an essential resource for all engineers either interested in or working on system designs. It was created by a recognized system design expert who not only teaches these principles daily but who brings years of hands on design expertise as the creator of some of the personal computer industries$1 (Bmost differentiated audio solutions(3y $1 (BJim Ganthier, Vice President of Marketing and Solutions, Industry Standard Servers- Hewlett-Packard (3z(BThis book helps designers by highlighting the pitfalls of high-speed systems design and providing solutions that improve the probability of success. Investing a small amount of time in the use of low-noise and low-radiation design methods from the very beginning of the development cycle will generate a high payoff by minimizing late-stage redesign costs and delays in the product ship date. To improve the probability of design success, applying the rules outlined in this book is a must-do.(3y$1 (BGene Frantz, Principle Fellow, Texas Instruments Incorporated. High-Speed DSP and Analog System Design is appropriate for advanced undergraduate and graduate students, researchers and professionals in signal processing and system design.s
Challenges of DSP Systems Design -- Transmission Line (TL) Effects -- Effects of Crosstalk -- Power Supply Design Considerations -- Power Supply Decoupling -- Phase-Locked Loop (PLL) -- Data Converter Overview -- Analog Filter Design -- Memory Sub-System Design Considerations -- Printed Circuit Board (PCB) Layout -- Electromagnetic Interference (EMI).
Keywords: Engineering; Electronics; Telecommunication; Systems engineering; Engineering; Signal, Image and Speech Processing; Circuits and Systems; Communications Engineering, Networks; Electronics and Microelectronics, Instrumentation